Blend of fluoropolymer and functional acrylic polymer as binder for electrochemical devices
A blend of PVDF with a functional acrylic copolymer addresses swelling issues and enhances adhesion/cohesion in lithium-ion battery electrodes, improving energy density and manufacturing efficiency by reducing binder content and solvent use.
Patent Information
- Application Number
- KR1020237041328
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-04-29
- Filing Date
- 2022-04-26
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2042-04-26
AI Technical Summary
Existing binders for lithium-ion batteries, such as PVDF and its copolymers, face issues with swelling when in contact with electrolytes, leading to electrode deterioration and inadequate adhesion/cohesion, and require high binder content to maintain structural integrity, which hinders energy density improvement.
A blend of a fluoropolymer, primarily PVDF, with a functional acrylic copolymer containing less than 10 mol% functional groups, such as carboxyl or hydroxyl groups, is used to enhance adhesion/cohesion, reducing the binder content while maintaining structural integrity and facilitating easier application on metal collectors.
The blend provides improved adhesion/cohesion, reduces the amount of organic solvent needed, and allows for higher active filler content, thereby increasing the energy density and manufacturing efficiency of lithium-ion battery electrodes.
Smart Images

Figure 112023133854564-PCT00001 
Figure 112023133854564-PCT00002 
Figure 112023133854564-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a blend of a fluoropolymer and an acrylic polymer for use as a binder or a coating of a separator of an electrode in an electrochemical device. Background Technology
[0002] PVDF and its copolymers, which are VDF-based fluoropolymers, are used as electrode binders or separator coatings in electrochemical devices, such as lithium-ion batteries. The most common use of PVDF in lithium-ion batteries is as a cathode binder, and it is often used as an anode binder as well. Another use of PVDF in lithium-ion batteries is as a coating layer on the separator. In the field of binders, one key property is the adhesion / cohesion of the composite electrode structure. A typical cathode in a lithium-ion battery consists of a composite porous structure containing an active material, a conductive carbon additive, and a binder, coated on aluminum foil. The adhesion / cohesion of the composite electrode can be characterized through a 180° peel test.
[0003] The active material for the lithium-ion battery cathode may be lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel-manganese-cobalt oxide, lithium nickel-cobalt-aluminum oxide, etc. The active material generally accounts for more than 90 wt% of the cathode composite. The conductive carbon additive may be carbon black, carbon fiber, carbon nanotube, graphite, graphene, etc. Its main function is to provide a conductive network to electrons, and its proportion in the cathode composite is generally 0.5 to 5 wt%.
[0004] In the general cathode of a lithium-ion battery, PVDF or a copolymer thereof is the primary binder used in the industry. The binder composition of the cathode is typically 0.5 to 5 wt%. One major requirement for the binder is to provide sufficient adhesion / cohesion to the composite electrode structure.
[0005] WO 9732347 describes an electrode for a battery comprising an electrode forming substrate containing a binder, wherein the binder describes an electrode used to be fixed to the collector surface of a battery. The binder comprises a PVDF (polyvinylidene fluoride) homopolymer or copolymer grafted with at least one acrylic polymer comprising an acrylic acid and / or methacrylic acid ester group, and the content of the grafted acrylic polymer is in the range of 0.1 to 20 wt% of the binder.
[0006] WO 9749777 discloses a binder that can be used to fix to a metal, comprising a polyvinylidene fluoride polymer, an acrylic or methacrylic polymer containing functional groups capable of fixing to a metal, and an acrylic or methacrylic type elastomer. This type of binder cannot be used in lithium-ion battery electrodes because the elastomer swells and the electrode is damaged when in contact with an electrolyte.
[0007] US 2013 / 252077 discloses an electrode for a lithium-ion battery operating with a non-aqueous electrolyte. The electrode comprises an active material and a binder comprising a vinylidene fluoride polymer and an acrylic polymer. Since the content of the acrylic polymer varies from 40 to 90 wt%, a problem arises in which the acrylic polymer in permanent contact with the electrolyte swells, particularly when the temperature of the electrode rises above the ambient temperature, causing the electrode to deteriorate.
[0008] Literature EP 2 953 193 discloses a binder for a lithium-ion battery comprising a fluoropolymer and an acrylic polymer containing nitrile groups.
[0009] Document WO 97 / 27260 discloses an electrode comprising a collector made of metal coated with a layer containing an active material and a binder. The binder comprises at least two of three components: a vinylidene fluoride polymer, an acrylic or methacrylic polymer containing functional groups capable of being immobilized on metal, and a vinylidene fluoride copolymer. When the binder comprises only the vinylidene fluoride polymer and the acrylic or methacrylic polymer, the acrylic or methacrylic polymer is present in a proportion ranging from 0.5 to 20 wt% of the total weight of the binder. In practice, it has been shown that the weight of the binder used must be sizable to obtain excellent cohesion of the active layer and excellent adhesion of the active layer to the metal collector. Additionally, swelling of the cathode in contact with the electrolyte is observed. The vinylidene fluoride copolymers considered in the document are Kynar® 500 and Kynar® 301 F. These copolymers exhibit a melt flow index (MFR) measured at 1.2 g / 10 min under 12.5 kg or 4 g / 10 min under 21.6 kg. Solutions of each of the copolymers at a concentration of 5 wt% in N-methyl-2-pyrrolidone exhibit a viscosity of 75 mPa·s at 23°C. These viscosity values were found to be unsuitable when the binder of the lithium-ion battery is used in a substrate layer coated on the metal collector of the battery at a content of less than 5 wt%.
[0010] In addition, it is known that a high molecular weight vinylidene fluoride homopolymer is used as a binder for lithium battery electrodes, and a 5% solution of said homopolymer in N-methyl-2-pyrrolidone exhibits a viscosity exceeding 100 mPa when measured at a controlled shear rate of 30 revolutions / min. This binder has the advantage of causing only limited swelling and having a low content of extractable material in the electrolyte. That is, during electrode use, a small amount of byproduct originating from the binder migrates into the electrolyte. This provides excellent adhesion due to the molecular weight of said PVDF homopolymer. On the other hand, since said same polymer has a high molecular weight, it has very high viscosity, and consequently, it is difficult to spread the paste formed by the mixture of said binder and the active material of the electrode onto a metal collector.
[0011] One example is the use of a functionalized acrylic additive as disclosed in U.S. patent application US 2018 / 0355206. US 2018 / 0355206 teaches that an acrylic copolymer having 10 mol% of an acid-containing monomer, namely methacrylic acid, yields better peeling.
[0012] Standard acrylic copolymers lack the stability required for application in batteries.
[0013] In the battery industry, there is a continuous demand for improvements in binder adhesion / cohesion to reduce binder loading and increase the overall energy density of batteries.
[0014] Surprisingly, the present invention demonstrates that an acrylic copolymer having less than 10 mol% of functional groups can significantly improve the adhesion / cohesion of a PVDF binder. The present invention also discloses that comonomers other than MAA can have a similar effect in increasing adhesion / cohesion. The present invention provides a blend of acrylic having a high Tg and PVDF, which provides a binder having excellent bonding adhesion for use in batteries.
[0015] The present invention relates to a polymer blend comprising a fluoropolymer and at least one functional acrylic copolymer. The fluoropolymer makes up the majority of the blend, comprising 80 wt% or more, preferably 90 wt% or more.
[0016] The fluoropolymer is preferably a polyvinylidene fluoride (PVDF) homopolymer or copolymer.
[0017] The functional acrylic copolymer is a poly(methyl methacrylate) copolymer containing more than 0.5 mol% and less than 10 mol%, preferably 0.5 to 8 mol%, more preferably 1 to 8 mol% of functional acrylic monomer units, and optionally containing hydrophobic monomers.
[0018] Functional acrylic polymers account for more than 1 wt% of the polymer blend.
[0019] Aspects of the invention
[0020] Embodiment 1: As a binder for a lithium-ion battery,
[0021] The above-mentioned binder for a lithium-ion battery comprises at least one vinylidene fluoride polymer and at least one acrylic copolymer, and
[0022] The above acrylic copolymer comprises a monomer having a functional group that exhibits affinity for metal or can be immobilized on metal, and
[0023] The above acrylic copolymer comprises a functional monomer having a Tg greater than 110C and comprising at least one type of functional group selected from the group consisting of carboxyl, hydroxyl, carboxylic acid anhydride, and epoxy, and
[0024] A 5 wt% solution of the vinylidene fluoride polymer in N-methyl-2-pyrrolidone exhibits a viscosity of 125 millipascal-seconds or more and less than 2,000 millipascal-seconds when measured at a controlled shear rate of 30 revolutions / min at 23°C, and
[0025] The above acrylic copolymer comprises less than 10 mol%, preferably 8 mol% or less, most preferably 7 mol% or less of a functional monomer, and
[0026] A binder in which a fluoropolymer constitutes more than 80 wt% of the total weight of the polymers in a polymer blend.
[0027] Embodiment 2: A binder of Embodiment 1, wherein the binder contains an acrylic copolymer in an amount of 2 wt% or more and 15 wt% or less of the total weight of the polymers in the polymer blend.
[0028] Embodiment 3: The binder of Embodiment 2, wherein the binder contains an acrylic copolymer in an amount of 10 wt% or less.
[0029] Embodiment 4: A binder of any one of Embodiments 1 to 3, wherein the viscosity of the 5 wt% PVDF solution is 300 millipascal-seconds or more and less than 1,500 millipascal-seconds.
[0030] Embodiment 5: A binder of any one of Embodiments 1 to 4, wherein the vinylidene fluoride polymer is a copolymer comprising hexafluoropropylene (HFP), tetrafluoroethylene (TFE), and at least one monomer selected from the group consisting of functionalized monomers, for example, vinyl carboxylic acid, phosphoric acid, sulfonic acid, and salt.
[0031] Embodiment 6: A binder of any one of Embodiments 1 to 5, wherein the molecular weight of the acrylic copolymer is greater than 80,000 g / mol, preferably greater than 100,000 g / mol.
[0032] Embodiment 7: A binder of any one of Embodiments 1 to 6 having high heat resistance when the Tg of the acrylic copolymer is measured to be greater than 110°C, preferably greater than 115°C, more preferably greater than 120°C.
[0033] Embodiment 8: A binder of any one of Embodiments 1 to 7, wherein the acrylic copolymer comprises a functional monomer having at least one type of functional group selected from the group consisting of carboxyl and hydroxyl.
[0034] Embodiment 9: A binder of any one of Embodiments 1 to 7, wherein the acrylic copolymer comprises a poly(methyl methacrylate) copolymer comprising a functional monomer having a carboxyl functional group.
[0035] Embodiment 10: A binder of any one of Embodiments 1 to 7, wherein the acrylic copolymer comprises methyl methacrylate units and methacrylic acid units.
[0036] Embodiment 11: A binder of any one of Embodiments 1 to 7, wherein the acrylic copolymer comprises a methyl methacrylate unit and a carboxyalkyl acrylate unit or a carboxyalkyl methacrylate unit.
[0037] Embodiment 12: A binder of any one of Embodiments 1 to 11, wherein the acrylic copolymer further comprises a hydrophobic monomer.
[0038] Embodiment 13: A binder of Embodiment 12, wherein the above hydrophobic monomer is an acrylic monomer having a cycloalkane group substituted therein.
[0039] Embodiment 14: A binder of Embodiment 12, wherein the hydrophobic monomer is selected from the group consisting of a carboxyalkyl acrylate monomer or oligomer, for example, tert-butyl cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, isobornyl methyl acrylate (IBOMA), and isobornyl acrylate (IBOA).
[0040] Embodiment 15: A binder of any one of Embodiments 1 to 14, wherein the mol% of the hydrophobic monomer unit is 0 to 15 mol%, preferably 0.5 to 10 mol%.
[0041] Embodiment 16: An electrode for a lithium-ion battery of a type comprising a metal collector, wherein at least one surface of the metal collector is coated with a substrate layer containing an active material and a binder of any one of Embodiments 1 to 15.
[0042] Embodiment 17: An electrode for a lithium-ion battery according to Embodiment 16, wherein the above-described material contains the binder in an amount of 0.5 wt% or more and 5 wt% or less.
[0043] Embodiment 18: An electrode for a lithium-ion battery according to Embodiment 16, wherein the above-described material contains the binder in an amount of 1 wt% or more and 3 wt% or less.
[0044] Embodiment 19: An electrode for a lithium-ion battery of any one of Embodiments 16 to 18, wherein the active material comprises lithium metal oxide and optionally carbon black.
[0045] Embodiment 20: An electrode for a lithium-ion battery of any one of Embodiments 16 to 18, wherein the active material comprises at least one component selected from coke, carbon black, graphite, activated carbon, and carbon fiber.
[0046] Embodiment 21: An electrode for a lithium-ion battery of any one of Embodiments 16 to 20, wherein the viscosity of the 5 wt% PVDF solution is 300 millipascal-seconds or more and less than 1,200 millipascal-seconds. Specific details for implementing the invention
[0047] The references cited in this application are incorporated herein by reference.
[0048] Percentages used herein are wt% unless otherwise specified, and molecular weight is weight-average molecular weight (Mw) unless otherwise specified. Molecular weight is measured by gel permeation chromatography (GPC) using a PMMA (polymethyl methacrylate) standard. Melt viscosity (MV) is measured at 230°C at 100 sec⁻¹. Glass transition temperature is measured using differential scanning calorimetry (DSC) under ASTM 3418, and the glass transition temperature of the acrylic polymer is measured at a heating rate of 10°C / min in N₂ during secondary heating. The first heating involves heating the sample to 170°C at a heating rate of 10°C / min, and then cooling the sample to 0°C at a cooling rate of 10°C / min. Melt viscosity is determined by capillary rheography at 230°C at 100 sec⁻¹ according to ASTM D3835.
[0049] "Copolymer" is used to mean a polymer having two or more different monomer units, including terpolymers and higher polymers. "Polymer" is used to mean both homopolymers and copolymers. For example, "PVDF" and "polyvinylidene fluoride" as used herein are used to mean both homopolymers and copolymers unless specifically stated otherwise. Polymers may be homogeneous, heterogeneous, or random, and may have a gradient distribution of comonomer units.
[0050] As used herein, “(meth)acrylate” or “(meth)acrylate” refers to both acrylate and methacrylate. (Meth)acrylate is used to refer to both acrylate and methacrylate, and mixtures thereof. The polymer may be linear, branched, star-shaped, comb-shaped, block-shaped, or any other structure.
[0051] "Amphiphilic polymers" are long-chain molecules that simultaneously contain hydrophobic and hydrophilic components.
[0052] The present invention relates to a binder comprising a functional acrylic polymer and PVDF, which can be used in a lithium-ion battery, and an associated electrode. The functional acrylic polymer preferably contains less than 10 wt%, more preferably 8 mol% or less, of functional monomer units in the functional acrylic polymer.
[0053] The present invention relates to a binder that can be used in a lithium-ion battery and comprises at least one vinylidene fluoride polymer and at least one acrylic copolymer, wherein the acrylic copolymer comprises a monomer having a functional group that exhibits affinity for a metal or can be immobilized on a metal. The acrylic copolymer is a copolymer of methyl methacrylate and a functional acrylic monomer.
[0054] The object of the present invention is to provide the aforementioned binder that imparts excellent adhesion between a metal and a PVDF-containing material layer.
[0055] Another objective of the present invention is to provide a binder that facilitates the manufacture of electrodes for lithium-ion batteries by easily spreading an active material onto a metal collector.
[0056] Another objective of the present invention is to provide a binder that reduces the amount of organic solvent used during the electrode processing step.
[0057] Another objective of the present invention is to provide an electrode for a lithium-ion battery.
[0058] Another objective of the present invention is to provide an electrode having a relatively low weight-based binder content so that the active filler content in the cathode can be increased to maximize the capacity of the battery.
[0059] bookbinder
[0060] The present invention relates to a polymer blend comprising a fluoropolymer and at least one functional acrylic copolymer for use as a binder in a battery. The fluoropolymer makes up the majority of the polymer blend and makes up 80 wt% or more, preferably 80 to 98 wt%, more preferably 90 to 98 wt%. Preferably, the binder contains the acrylic copolymer in an amount of 2 wt% or more and 20 wt% or less, particularly 15 wt% or less or 10 wt% or less, based on the total polymer of the binder.
[0061] Blending a functional acrylic polymer with a fluoropolymer provides improved mechanical performance, for example, increased adhesion through dipole-dipole interactions between PVDF and the acrylic copolymer. The fluoropolymer / acrylic blend of the present invention is suitable for applications as electrode binders or separator coatings for lithium-ion batteries where improved adhesion / cohesion or bond strength is required. The functional acrylic copolymer is composed of monomer units having a functional group in the acrylic copolymer in an amount of less than 10 mol%, preferably less than 8 mol%. The mol% of the functional monomer in the acrylic polymer is 0.5 to less than 10 mol%, preferably 1 to 8 mol%. Preferably, the functional group is a carboxylic acid functional group.
[0062] The presence of the acrylic copolymer is thought to facilitate the application of the active material during the manufacture of the electrode, resulting in a reduction in the viscosity of the binder / active material mixture. Furthermore, as a result of the reduction in the viscosity of the binder, and thus the binder / active material mixture, the amount of organic solvent required for the manufacture of the electrode is reduced, and thus the use of the binder according to the present invention is more eco-friendly.
[0063] The binder of the present invention does not contain an elastomeric polymer or an elastomeric copolymer, in particular an acrylic-type elastomeric (co)polymer, and the acrylic-type polymer is not an elastomeric polymer.
[0064] The fluoropolymer / acrylic blend of the present invention is not an acrylic-modified fluoropolymer as described in US6680357 or US6635714. In the present invention, polymers polymerized in separate polymerization processes are mixed or blended together through physical means.
[0065] Fluoropolymer
[0066] The PVDF of the present invention is a vinylidene fluoride homopolymer or copolymer having vinylidene fluoride monomer units in an amount greater than 50 wt%, preferably greater than 65 wt%, more preferably greater than 75 wt%, and most preferably greater than 90 wt%.
[0067] Vinylidene fluoride polymer copolymers include those containing at least 50 wt%, preferably at least 75 wt%, more preferably at least 80 wt%, and more preferably at least 90 wt% of vinylidene fluoride copolymerized with one or more comonomers. Exemplary comonomers include tetrafluoroethylene (TFE), trifluoroethylene (TrFE), chlorotrifluoroethylene (CTFE), 1,2-difluoroethylene, perfluorobutylethylene (PFBE), hexafluoropropene (HFP), vinyl fluoride (VF), pentafluoropropene, tetrafluoropropene, trifluoropropene, fluorinated (alkyl) vinyl ethers, e.g., perfluoroethyl vinyl ether (PEVE) and perfluoro-2-propoxypropyl vinyl ether, perfluoromethyl vinyl ether (PMVE), perfluoropropyl vinyl ether (PPVE), perfluorobutyl vinyl ether (PBVE), long-chain perfluorovinyl ethers, and any other monomer that readily copolymerizes with vinylidene fluoride, partially or entirely fluorinated alpha-olefins, e.g., 3,3,3-trifluoro-1-propene, 2-trifluoromethyl-3,3,3-trifluoropropene, The polymer may be selected from the group consisting of 1,2,3,3,3-pentafluoropropene, 3,3,3,4,4-pentafluoro-1-butene, hexafluoroisobutylene (HFIB), fluorinated dioxols, for example, one or more of perfluoro(1,3-dioxol) and perfluoro(2,2-dimethyl-1,3-dioxol) (PDD), C4 or more partial- or per-fluorinated alpha-olefins, C3 or more partial- or per-fluorinated cyclic alkenes, and higher allyl, partial-fluorinated allyl or fluorinated allyl monomers, for example, 2-hydroxyethylallyl ether or 3-allyloxypropanediol, and ethene or propene and combinations thereof. Other monomer units of the polymer may comprise any monomer containing a polymerizable C=C double bond.Additional monomers may be 2-hydroxyethyl allyl ether, 3-allyloxypropanediol, allyl monomer, ethene or propene, acrylic acid, or methacrylic acid.
[0068] In one preferred embodiment, the fluoropolymer is an acid-functionalized fluoropolymer, preferably acid-functionalized PVDF.
[0069] Methods for preparing acid-functionalized fluoropolymers are known in the art. WO2019 / 199753, WO2016149238, and US 8,337,725 provide some known methods for preparing acid-functionalized fluoropolymers, the contents of which are incorporated herein by reference.
[0070] In one embodiment, up to 30 wt%, preferably up to 25 wt%, more preferably up to 15 wt% of hexafluoropropene (HFP) units and 70 wt% or more, preferably 75 wt% or more, more preferably 85 wt% or more of VDF units are present in the vinylidene fluoride polymer.
[0071] Preferably, the vinylidene fluoride polymer makes the viscosity of an N-methyl-2-pyrrolidone solution containing 5 wt% of the vinylidene fluoride polymer to be 125 mPa·s or more, preferably 300 mPa·s or more, preferably 300 mPa·s or more and less than 2,000 mPa·s, less than 1,500 mPa·s, preferably less than 1,200 mPa·s, when measured at a controlled shear rate of 30 revolutions / min at 23°C.
[0072] The above type of vinylidene fluoride polymer has a molecular weight of up to 1 million g and is already being used as a binder for lithium-ion batteries. A mixture of the vinylidene fluoride polymer and an acrylic copolymer can lower the viscosity of the binder, thereby lowering the viscosity of the paste used to manufacture lithium-ion battery electrodes, and thus making it easier to manufacture the electrodes. Nevertheless, it was not evident that adding a functionalized acrylic polymer in an amount of less than 10 wt%, preferably less than 8 wt%, and having a molar mass much lower than that of PVDF, would significantly increase adhesion. This is because it is known to those skilled in the art that the higher the molar mass of the binder, the more satisfactory the adhesion of the binder to the metal plate, and the cohesiveness of the electrode containing the binder is also improved.
[0073] It is possible to manufacture an electrode for a lithium-ion battery containing a reduced amount of binder, thereby increasing the active filler content of the cathode and increasing the charging capacity of the cathode.
[0074] acrylic polymer
[0075] The acrylic polymer of the present invention comprises mostly polymethylacrylate monomer units (greater than 50%, preferably greater than 80 mol%), and said acrylic polymer comprises acrylic monomer units having a functional group ("functional monomer") in an amount of less than 10 mol%, preferably 8 mol% or less, or 7 mol% or less. Functional groups capable of being immobilized on a metal or exhibiting an affinity for a metal are widely known to those skilled in the art. The said functional group may contain at least one type of group selected from, for example, carboxylic acid, hydroxyl, carboxylic anhydride, and epoxy groups. Preferably, the acrylic copolymer comprises a monomer comprising a carboxylic acid functional group or a carboxyl functional group, most preferably a carboxylic acid functional group.
[0076] In some embodiments, the acrylic copolymer comprises carboxyalkyl acrylate or carboxyalkyl methacrylate units.
[0077] Non-limiting examples of monomers having functional groups include (meth)acrylic acids, e.g., 2-carboxyethyl acrylate (CEA), acrylic acid, and methacrylic acid.
[0078] In some embodiments, the acrylic copolymer comprises hydrophobic monomer units in addition to monomers containing functional groups to produce an amphiphilic acrylic copolymer. The mol% of the hydrophobic monomer units is 0 to 15 mol%, 0.5 to 10 mol%, or 0.5 to 8 mol%. One example of the hydrophobic monomer is an acrylic monomer having a substituted cycloalkane group.
[0079] In some embodiments, the hydrophobic acrylic copolymer comprises carboxyalkyl acrylate monomer units or oligomers, for example, tert-butyl cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, isobornyl methyl acrylate (IBOMA) and isobornyl acrylate (IBOA).
[0080] The acrylic copolymer may optionally contain additional acrylate and methacrylate monomers or other ethylene unsaturated monomers, including but not limited to styrene, alpha-methyl styrene, and acrylonitrile. Suitable acrylate and methacrylate comonomers include, but are not limited to, methyl acrylate, ethyl acrylate and ethyl methacrylate, butyl acrylate and butyl methacrylate, iso-octyl methacrylate and iso-octyl acrylate, lauryl acrylate and lauryl methacrylate, stearyl acrylate and stearyl methacrylate, isobornyl acrylate and isobornyl methacrylate, methoxyethyl acrylate and methoxy methacrylate, 2-ethoxyethyl acrylate and 2-ethoxyethyl methacrylate, and dimethylaminoethyl acrylate and dimethylaminoethyl methacrylate monomers.
[0081] In some embodiments, the acrylic polymer is a PMMA / hydrophilic 2-carboxyethyl acrylate (CEA) polymer having a Tg greater than 100°C and a MW greater than 100,000 g / mol. In some embodiments, the acrylic polymer is a PMMA / hydrophilic 2-carboxyethyl acrylate (CEA) polymer further comprising a hydrophobic monomer unit selected from the group of tert-butyl cyclohexyl methacrylate, 3,3,5-trimethylcyclohexyl(meth)acrylate, isobornyl methyl acrylate (IBOMA), and isobornyl acrylate (IBOA), having a Tg greater than 100°C and a MW greater than 100,000 g / mol. High-temperature acrylic copolymers containing functional CEA maintain a high Tg and improve bond adhesion.
[0082] Acrylic copolymers have high heat resistance, with a Tg of greater than 110°C, preferably greater than 115°C, more preferably greater than 120°C when measured, and generally the Tg is in the range of 110 to 140°C.
[0083] The weight average molecular weight of the acrylic copolymer is greater than 65,000 g / mole, preferably greater than 80,000 g / mole, and more preferably greater than 100,000 g / mole.
[0084] Acrylic copolymers or mixtures of acrylic (co)polymers are not elastomers. That is, they do not exhibit a glass transition temperature of less than 20°C.
[0085] Advantageously, the acrylic copolymer contains less than 10 mol% of monomers having functional groups, preferably groups that exhibit affinity for metal or can be immobilized on metal, preferably acid functional groups, in an amount of 8 mol% or less, and optionally contains hydrophobic monomers. The applicant of the present invention has demonstrated that such copolymer can impart excellent adhesion to a material containing said copolymer and deposited on a metal sheet.
[0086] electrode
[0087] The present invention also relates to an electrode for a lithium-ion battery of the type comprising a metal collector, wherein at least one surface of the metal collector is coated with a substrate layer containing an active material and a binder, and the binder characteristically comprises a binder according to the present invention or is composed of a binder according to the present invention.
[0088] Active materials that can be used to form an anode or cathode are widely known to those skilled in the art.
[0089] The electrode may be a cathode, in which case the substrate may contain lithium metal oxide and optionally carbon black as an active material.
[0090] The electrode may be an anode, in which case the above material may contain at least one component selected from coke, carbon black, graphite, activated carbon, and carbon fiber as an active material.
[0091] Solution viscosity is measured using a Brookfield rotational viscometer containing an SC4-34 type spindle.
[0092] The present invention, the features provided by the present invention, and the various advantages will become more apparent by reading the following embodiments provided as illustrative and non-limiting examples.
[0093] Examples
[0094] PVDF1 is a VDF homopolymer having a melt viscosity of 4,450 to 5,450 Pa-s at 230°C and 100s-1 according to ASTM D3835.
[0095] Acrylic PMMA-MAA with an MAA content of 10% or less is added to a PVDF base binder in an amount of <0.1 to 10 wt%. An example of the base PVDF was PVDF1 for cathode binder application. The functionalized PMMA copolymers used in the examples and their main properties are listed in Table 1.
[0096]
[0097] Preparation of polymer blend binder solution
[0098] 92 g of N-methyl-2-pyrrolidone (NMP, bio-grade from Alfa Aesar) was added to 8.0 g of PVDF1 and mixed overnight at ~60°C in a heated roll mixer to prepare an 8.0 wt% PVDF solution. 1.0 g of acrylic copolymer was dissolved in 11.5 g of NMP and mixed in the same manner to prepare an 8.0 wt% acrylic solution.
[0099] One method for creating a homogeneous polymer blend is solution blending. Appropriate amounts of PVDF solution and acrylic solution were added to a vil and rolled overnight. For example, to make a 95:5 PVDF / acrylic blend solution, 19 g of 8wt% PVDF solution and 1 g of 8wt% acrylic solution were mixed together. In all cases, the total binder (PVDF + acrylic) concentration is 8.0wt%.
[0100] Cathode formulation and manufacturing
[0101] Two exemplary cathode slurry preparation procedures for laboratory scale are described here. Method #1 involves mixing carbon black and a binder solution first, and then mixing with the active material. Method #2 involves mixing carbon black and the active material as dry powders, and then mixing with the binder solution. Both methods are used in the lithium-ion battery industry. The following procedure is for laboratory scale using a target formulation of dry standard NMC622 / SuperP / binder = 97 / 1.5 / 1.5.
[0102] Slurry Method #1
[0103] 0.36g of Timcal’s SuperP-Li, a conductive carbon additive, is added to 4.5g of an 8.0% binder solution and mixed three times using a centrifugal planetary mixer Thinky AR-310 at 2,000 rpm for 120 seconds, with 1 minute of air cooling in between. Once the conductive carbon is dispersed in the binder solution, 23.28g of the active material Celcore® NMC622 (Umicore) and a small amount of NMP (0.5g) are added to the mixture and mixed for 60 seconds at 2,000 rpm to form a thick, uniform paste. Then, a small amount of NMP (0.5g) is added to the paste and mixed at 60 seconds / 2,000 rpm to gradually reduce the slurry's solid content and viscosity. This dilution step is repeated several times until the slurry viscosity reaches a level suitable for coating, typically 3,000 to 15,000 cP @ 1 / s shear rate. Generally, the final solid content level of the NMC622 / SuperP / binder = 97 / 1.5 / 1.5 formulation is about 80 wt%.
[0104] Electrode casting and drying
[0105] Next, the cathode slurry is cast onto aluminum foil (current collector, 15 µm thick) at a coating speed of 0.3 m / min using the adjustable doctor blade of an automatic film applicator (Elcometer 4340). The doctor blade spacing is set to a dry thickness of approximately 80 µm or approximately 200 g / m² 2 It is empirically adjusted to provide the mass loading. Then, the wet casting is transferred to a convection oven and dried at 120°C for 30 minutes. After drying, the electrode is calendered using a roll mill (Hohsen HSTK-1515H), and the final density of the NMC622-based electrode is typically about 3.4 g / cm³. 3 am.
[0106] Peel test
[0107] For the peel test, the sample is cut into 1-inch wide stripes 5 to 8 inches long. The sample is dried overnight in a vacuum oven at ~85°C and then stored in a drying chamber. The peel strength of the cathode was obtained via a 180° peel test using ASTM D903 with several modifications. The first modification was that the elongation rate used was 50 mm / min (peeling rate 25 mm / min). The second modification was to dry the test sample prior to the peel test (as described above) and to perform the peel test inside the drying chamber, as variations in exposure to ambient moisture can significantly affect the peel results. The 1-inch wide test stripe is adhered to an alignment plate via 3M 410M double-sided paper tape, and the flexible aluminum foil current collector device is peeled off by the grip of the test instrument. The mechanical tester is an Instron 3343 model equipped with a 10N load cell. Peel results are reported in N / m.
[0108] Example 1:
[0109] A cathode was prepared using Slurry Method 1, utilizing solution-blended PVDF1 / PMMA1 at various ratios or additive levels ranging from 2 to 6 wt% based on the total binder (PVDF1 + acrylic). The active material used was Celcore® NMC622, the carbon additive was Super-P, and the cathode composition was NMC622 / SuperP / binder = 97 / 1.5 / 1.5 on a dry basis. The mass load of the cathode example was approximately 205 g / m² 2 It was, and the final compressed density was approximately 3.4 g / cm³. 3 was.
[0110] There are various factors that can affect the absolute value of the peel test results. For example, ambient conditions (humidity and temperature) during slurry preparation, the slurry mixing protocol, and the peel sample conditioning protocol can all have a significant effect on the absolute value. It is more meaningful to compare the relative valve with a control group, in which case the inventors selected the solvent-free PVDF PVDF1 sample as the control group. The ambient conditions for the examples are 26 to 29°C and RH ~12%.
[0111] Comparative Example 1:
[0112] The same method as in Example 1 was followed, except that the binder was solvent-free battery grade PVDF1 containing no additives.
[0113]
[0114] The level of addition significantly affects the final peel strength of the cathode composite. In this case, the minimum level of addition is greater than 2 wt%. When a small amount (4 to 6 wt%) of PMMA1 is added to PVDF1, the peel strength increases by 39 to 56% compared to the PVDF1 control group. PMMA1 containing 4.5 wt% of MAA comonomer had a Tg of 122°C when measured by DSC. The weight-average molecular weight (Mw) of the resin was measured to be 85,000 g / mole using GPC, and the Mw / Mn (polydispersity) value was 1.9.
[0115] For comparison purposes, the following examples all use a level of 5 wt% (PVDF1 / additive = 95 / 5).
[0116] Example 2
[0117] The binder used is PVDF1 / PMMA2 with a 95 / 5 blend ratio obtained through solution blending. PMMA2 is PMMA-MAA with a larger molecular weight than PMMA1. The cathode was prepared using slurry procedure #1 and has a nominal composition of NMC622 / SuperP / binder = 97 / 1.5 / 1.5 on a dry basis. The mass load of the cathode example is approximately 205 g / m² 2 was, and the final compressed density was approximately 3.4 g / cm³ 3 was.
[0118] A PMMA2 copolymer containing 6 wt% MAA was produced by bulk polymerization at 160°C when the conversion rate was >50%. The glass transition temperature of the resin was measured at 126°C using DSC in N2 at a heating rate of 10°C / min. The weight-average molecular weight (Mw) of the resin was 115,000 g / mole when measured using GPC, and the Mw / Mn (polydispersity) value was 1.9.
[0119] Comparative Example 2
[0120] The same method as in Example 2 was followed, except that the additive was PMMA5, said PMMA5 is a PMMA5 (ethyl acrylate) copolymer. PMMA5 containing 0.6 wt% EA had a Tg of 114°C when measured by DSC. The weight average molecular weight (Mw) of the resin was 109,000 g / mole when measured using GPC, and the Mw / Mn (polydispersity) value was 1.9.
[0121] Example 3
[0122] The same method as in Example 2 was followed except that the additive was PMMA3, said PMMA3 is an amphiphilic, higher molecular weight, and third monomer that fine-tunes the dipole-dipole interaction with PVDF.
[0123] A PMMA3 copolymer containing 4 wt% MAA and 1.5 wt% tert-butyl cyclohexyl methacrylate (Sartomer BCHMA) was prepared by mass polymerization at 160°C when the conversion rate was >50%. The glass transition temperature of the resin was measured at 121°C using DSC in N2 at a heating rate of 10°C / min. The weight-average molecular weight (Mw) of the resin was 105,000 g / mole when measured using GPC, and the Mw / Mn (polydispersity) value was 1.9.
[0124] Example 4
[0125] The same method as in Example 2 was followed, except that the additive was PMMA4, said PMMA4 is an acrylic copolymer having 2-carboxyethyl acrylate instead of MAA.
[0126]
[0127] PMMA4 copolymer prepared by solution polymerization in toluene at 70°C: This example demonstrates the preparation of a high molecular weight copolymer of methyl methacrylate and 2-carboxyethyl acrylate. 94.80 parts of methyl methacrylate and 5.20 parts of 2-carboxyethyl acrylate (2-CEA from Aldrich) were loaded into a reaction vessel containing 300 parts of toluene at a mechanical stirring speed of 380 rpm near 23°C. AIBN (manufactured by Aldrich) was used as an initiator at a level of 0.241 parts. The polymerization reaction was carried out at 65 to 68°C for 6 hours. When the conversion rate reached >50%, the residual monomer was removed by precipitation in methanol (MeOH, 20 times). Subsequently, the solid polymer powder was dissolved in acetone to a solid content of 25 wt%, and the polymer solution was precipitated again in sufficient MeOH. The reprecipitated white powder sample was dried in a vacuum oven at 180°C for 16 hours.
[0128] The glass transition temperature of the resin was measured using DSC in PMMA4 N2 at a heating rate of 10℃ / min and was 123℃. The weight-average molecular weight (Mw) of the resin was 130,000 g / mole when measured using GPC, and the Mw / Mn (polydispersity) value was 1.8.
[0129] Ambient environmental conditions may affect the absolute value of peeling. The relative value is not affected. Examples 2 to 4 and comparative examples were carried out under the same ambient environmental conditions.
[0130]
[0131] When a small amount (5 wt%) of different acid-functional acrylic copolymers was blended into a PVDF1 base resin, the mechanical peel strength increased dramatically to 39 to 84% compared to the PVDF1 control.
[0132] Comparative Example 2 is PVDF1 blended with PMMA5, which lacks acid functional groups, and as can be seen, the effect of increasing peel strength is somewhat limited compared to other acrylic copolymers containing acid-functional monomers of Examples 2, 3, and 4. Example 2 showed improved peel strength due to its higher molecular weight. Example 3, containing PMMA3, has a higher Mw and includes a third monomer that modulates dipole-dipole interactions with PVDF, which demonstrates a significant improvement in peel strength. Example 4 shows 2-carboxyethyl acrylate (CEA), which can provide improvements similar to those of the MAA commoner.
[0133] Peeling tests for Examples 5 to 7 were conducted under similar ambient environmental conditions to allow for comparison of the results.
[0134] Example 5 (functional pMMA copolymer containing 2-CEA blended with PVDF1).
[0135] A blended dry coating (97.8 / 2.2 wt / wt) copolymer of 95 wt% PVDF1 and 5 wt% pMMA / 2-carboxyethyl acrylate (Tg = 123C, MW = 130,000) exhibited a peel adhesion strength of 180 N / m against the Al foil of the battery cathode binder, compared to 105 N / m of the PVDF1 control, using a 180-degree peel adhesion test.
[0136] Example 6 (functional pMMA copolymer containing 2-CEA + MAA blended with PVDF1)
[0137] A blended dry coating (96.9 / 2.1 / 1.0 w / w / w) copolymer of 95 wt% PVDF1 (manufactured by Arkema) and 5 wt% pMMA / 2-carboxyethyl acrylate / MAA (Tg = 125C, MW = 140,000) exhibited peel adhesion to the Al foil of the battery cathode binder, compared to 105 N / m of the PVDF1 control, using a 180-degree peel adhesion test.
[0138] Example 7 (functional pMMA copolymer containing 2-CEA + SR218A blended with PVDF1)
[0139] A blended dry coating (96.9 / 2.6 / 0.5 w / w / w) copolymer of 95 wt% PVDF1 (manufactured by Arkema) and 5 wt% pMMA / 2-carboxyethyl acrylate / tert-butyl cyclohexyl methacrylate (Tg = 124C, MW = 135,000) exhibited a peel bond adhesion strength of 127 N / m against the Al foil of the battery cathode binder, compared to 105 N / m of the PVDF1 control, using a 180-degree peel adhesion test.
Claims
Claim 1 A binder for a lithium-ion battery, wherein the binder for a lithium-ion battery comprises at least one vinylidene fluoride polymer and at least one acrylic copolymer, wherein the acrylic copolymer comprises a functional monomer selected from the group consisting of hydroxyl, carboxylic acid anhydride, and epoxy and comprising at least one type of functional group that exhibits affinity for a metal or can be immobilized on a metal, wherein the acrylic copolymer has a Tg greater than 110°C, and a 5 wt% solution of the vinylidene fluoride polymer in N-methyl-2-pyrrolidone exhibits a viscosity of 125 millipascal-seconds or more and less than 2,000 millipascal-seconds when measured at a controlled shear rate of 30 revolutions / min at 23°C, wherein the acrylic copolymer comprises less than 10 mol%, or 8 mol% or less, or 7 mol% or less of the functional monomer, and the fluoropolymer constitutes more than 80 wt% of the total weight of the polymers in the polymer blend. Claim 2 A binder according to claim 1, wherein the binder contains an acrylic copolymer in an amount of 2 wt% or more and 15 wt% or less of the total weight of the polymers in the polymer blend. Claim 3 In paragraph 2, the binder comprises an acrylic copolymer having a content of 10 wt% or less. Claim 4 A binder according to claim 1, wherein the viscosity of the 5 wt% vinylidene fluoride polymer solution is 300 millipascal-seconds or more and less than 1,500 millipascal-seconds. Claim 5 A binder according to claim 1, wherein the vinylidene fluoride polymer is a copolymer comprising at least one monomer selected from the group consisting of hexafluoropropylene (HFP), tetrafluoroethylene (TFE), vinyl carboxylic acid, phosphoric acid, sulfonic acid, and salts thereof. Claim 6 A binder according to claim 1, wherein the molecular weight of the acrylic copolymer is greater than 80,000 g / mol or greater than 100,000 g / mol. Claim 7 A binder according to any one of claims 1 to 6, wherein the Tg of the acrylic copolymer is greater than 110°C, or greater than 115°C, or greater than 120°C. Claim 8 A binder according to any one of claims 1 to 6, wherein the acrylic copolymer comprises a functional monomer having at least one type of functional group selected from the group consisting of carboxyl and hydroxyl. Claim 9 A binder according to any one of claims 1 to 6, wherein the acrylic copolymer comprises a poly(methyl methacrylate) copolymer comprising a functional monomer having a carboxyl functional group. Claim 10 A binder according to any one of claims 1 to 6, wherein the acrylic copolymer comprises methyl methacrylate units and methacrylic acid units. Claim 11 A binder according to any one of claims 1 to 6, wherein the acrylic copolymer comprises a methyl methacrylate unit and a carboxyalkyl acrylate unit or a carboxyalkyl methacrylate unit. Claim 12 A binder according to any one of claims 1 to 6, wherein the acrylic copolymer further comprises a hydrophobic monomer. Claim 13 In claim 12, the binder is an acrylic monomer having a cycloalkane group substituted with the hydrophobic monomer. Claim 14 A binder according to claim 12, wherein the hydrophobic monomer comprises a carboxylalkyl acrylate monomer or an oligomer. Claim 15 A binder according to claim 12, wherein the hydrophobic monomer is selected from the group consisting of tert-butyl cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, isobornyl methyl acrylate (IBOMA), and isobornyl acrylate (IBOA). Claim 16 A binder according to claim 12, wherein the mol% of the hydrophobic monomer unit is 0 to 15 mol% or 0.5 to 10 mol%. Claim 17 An electrode for a lithium-ion battery of a type comprising a metal collector, wherein at least one surface of the metal collector is coated with a substrate layer containing an active material and a binder described in any one of claims 1 to 6. Claim 18 An electrode for a lithium-ion battery according to claim 17, wherein the above description contains the binder in an amount of 0.5 wt% or more and 5 wt% or less. Claim 19 An electrode for a lithium-ion battery according to claim 17, wherein the above description contains the binder in an amount of 1 wt% or more and 3 wt% or less. Claim 20 An electrode for a lithium-ion battery according to claim 17, wherein the active material comprises lithium metal oxide and optionally carbon black. Claim 21 An electrode for a lithium-ion battery according to claim 17, wherein the active material of the above-described layer comprises at least one component selected from coke, carbon black, graphite, activated carbon, and carbon fiber. Claim 22 An electrode for a lithium-ion battery according to claim 17, wherein the acrylic copolymer further comprises a hydrophobic monomer or an acrylic monomer having a substituted cycloalkane group.
Citation Information
Patent Citations
Binder and related lithium-ion battery electrodes containing polyvinyliden fluoride that can be fixed to metal
KR1020180081815A
Hydrophobic high heat optical acrylic copolymers
WO2020206113A1
